Correlation between Redrying Conditions and Electrode Properties in LiFePO4 Cathode - Hotaru YAMAGUCHI; Yumi NISHIYAMA; Chihiro SHINODA; Yuki UEDA; Junpei TERADA; Shigeaki YAMAZAKI (Electrochemistry)
Recently, improving the performance and reducing the cost of lithium-ion batteries (LIBs) have become critical challenges. LiFePO4 (LFP), in particular, has gained significant attention as a low-cost with high-performance cathode material, contributing to excellent cycle stability, safety, and environmental sustainability. The total cost of LIBs is not determined solely by material costs, and the manufacturing processes, such as production speed and yield rate, also have substantial impacts. To increase the production speed of electrodes, the improvements such as raising the drying temperature of the cathode slurry and manufacturing electrodes at high speeds have been investigated. Nonetheless, understanding the challenges associated with scaling up seems to be difficult from the laboratory scale. In this paper, we focus on the physical property changes due to drying temperature, a factor with a significant impact on the manufacturing process, using the polyvinylidene difluoride (PVDF) and polyvinylidene difluoride-tetrafluoroethylene copolymer (NEOFLON VT-475) as fluoropolymer binders for LFP cathode. The results show that the electrodes with PVDF exhibited significant changes in peeling strength of electrode/current collector interface, as well as in electrode flexibility, depending on the drying temperature. On the other hand, the electrodes with VT-475 demonstrated minimal physical property changes with varying drying temperatures, and a reduction in binder quantity was feasible, suggesting a potential contribution to reducing battery costs.